Is visual reliance increased in athletes after ACL injury? A scoping review - Tortoli, E.; Gokeler, A.; Tak, I. (Sports Medicine, 2024)
Background: Individuals with anterior cruciate ligament (ACL) injury often exhibit visual cognitive deficits during tasks that require neuromuscular control. In this paper, we present evidence of increased visual reliance after ACL injury during a range of clinically applicable cognitive-motor tasks. This information is essential to strengthen the scientific rationale for therapeutic interventions that target maladaptive neuroplasticity and may translate to improved return-to-sport (RTS) outcomes following ACL injury. Objectives: The objectives of this study are (1) to determine if visual reliance is present during common rehabilitation-based assessments after ACL deficiency (ACL-D) or ACL reconstruction (ACL-R), (2) to describe how visual reliance is assessed during such tasks, and (3) to provide information to help clinicians and patients understand the clinical relevance of cognitive load in the assessment and intervention of visual reliance. Design: Scoping review. Literature search: We searched MEDLINE, EMBASE, CINAHL, SCOPUS, and PEDro databases. Study selection criteria: Only primary studies published in English were included without time limitations. Data synthesis: Qualitative analysis of the included studies was performed. Results: We synthesized the results of 23 studies. A total of 7 studies (31%) included patients with ACL-D, 15 studies (65%) included patients with ACL-R, and 1 study (4%) included patients with ACL-D and ACL-R. Evaluation of tasks, task evaluation setting, visual conditions, outcome measures, and presence of increased visual reliance were identified. Most studies investigating patients with ACL-D, contrary to those with ACL-R, exhibited worse postural stability during eyes-closed conditions than uninjured controls. Complete visual obstruction (i.e., eyes closed or blindfolded) was the most frequently reported method to disrupt vision (52%). The addition of a visual-cognitive challenge resulted in significantly worse postural stability in patients with ACL-R compared with controls. Conclusions: Visual reliance was most commonly assessed during single leg stance with complete visual obstruction. The majority of studies on patients with ACL-D indicate that they exhibit poorer postural stability in eyes-closed conditions when compared with uninjured controls, which suggests increased visual reliance. There is less evidence of visual reliance in patients who have undergone ACL-R compared with those with ACL-D. Adding a visual-cognitive load was found to be more effective in inducing postural stability deficits in individuals who have undergone ACL-R.